2017
DOI: 10.1093/nar/gkx878
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic DNA binding, junction recognition and G4 melting activity underlie the telomeric and genome-wide roles of human CST

Abstract: Human CST (CTC1-STN1-TEN1) is a ssDNA-binding complex that helps resolve replication problems both at telomeres and genome-wide. CST resembles Replication Protein A (RPA) in that the two complexes harbor comparable arrays of OB-folds and have structurally similar small subunits. However, the overall architecture and functions of CST and RPA are distinct. Currently, the mechanism underlying CST action at diverse replication issues remains unclear. To clarify CST mechanism, we examined the capacity of CST to bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 62 publications
8
118
0
Order By: Relevance
“…This is similar to what has been reported in CTC1 deficient mouse embryonic fibroblasts (Gu et al, 2012). Co-immunostaining of 53BP1 and TRF1 showed that the correlations of the sub-nuclear localizations of these proteins were not different among LCLs derived from the patient, heterozygous parents or controls, supporting the notion that genomic instability caused by aberrant CTC1 function is not limited to the telomeres, but extends to additional regions of the genome (Bhattacharjee et al, 2017;Y. Wang & Chai, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to what has been reported in CTC1 deficient mouse embryonic fibroblasts (Gu et al, 2012). Co-immunostaining of 53BP1 and TRF1 showed that the correlations of the sub-nuclear localizations of these proteins were not different among LCLs derived from the patient, heterozygous parents or controls, supporting the notion that genomic instability caused by aberrant CTC1 function is not limited to the telomeres, but extends to additional regions of the genome (Bhattacharjee et al, 2017;Y. Wang & Chai, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…However, continuous cellular replication in tissues with limiting DNA Pol‐α levels results in C‐strand maintenance defects, manifested as stalled replication forks unable to bypass G‐rich secondary structures including G‐quadruplexes (G4), resulting in the formation of single‐stranded gaps that when degraded give rise to STL. Both POT1 and CST efficiently disrupt G‐quadruplex formation in vitro (Bhattacharjee, Wang, Diao & Price, 2017; Wang, Nora, Ghodke & Opresko, 2011), and our data suggest that introduction of WT CTC1 into CTC1 L1142H mutants completely suppressed STL formation (Figure 3g). We postulate that CST/POT1 plays an important role in preventing the formation of G4 on ss telomeric G‐rich DNA to maintain genome stability.…”
Section: Discussionsupporting
confidence: 53%
“…MRE11 possesses the 3' to 5' exonuclease activity and can extensively degrade ss-ds DNA junction structures with 5' overhangs formed by regressed forks (Kolinjivadi et al, 2017). It has been reported that CST prefers binding to ss-ds DNA junctions in vitro (Bhattacharjee et al, 2017). Hence, we hypothesized that CST might bind to 5' overhangs of the regressed arms to protect nascent strand DNA from MRE11 degradation.…”
Section: Nascent Strand Degradation Caused By Cst Deficiency Requiresmentioning
confidence: 99%
“…It is capable of binding to an 18-nt G-rich ssDNA with high affinity, but the sequence specificity is lost if the oligonucleotide becomes longer (Hom & Wuttke, 2017;Miyake et al, 2009). Interestingly, although CST is unable to bind to dsDNA, ss-ds DNA junctions stabilize CST binding and decrease minimal ssDNA length requirement for CST binding to 10 nt (Bhattacharjee et al, 2017), indicating that CST may bind to special DNA structures with ss-ds junctions in vivo. A set of missense mutations of CTC1 and STN1 genes have been identified in patients with the Coats plus disease, a rare autosomal recessive disorder characterized by bilateral exudative retinopathy, retinal telangiectasias, growth retardation, intracranial calcifications, bone abnormalities, gastrointestinal vascular ectasias, accompanied by common early-aging pathological features (Anderson et al, 2012;Keller et al, 2012;Simon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%